2014
DOI: 10.1002/jbmr.2237
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Vitamin A and Risk of Fracture: Meta-Analysis of Prospective Studies

Abstract: Osteoporotic fracture is a significant cause of morbidity and mortality and is a challenging global health problem. Previous reports of the relation between vitamin A intake or blood retinol and risk of fracture were inconsistent. We searched Medline and Embase to assess the effects of vitamin A (or retinol or beta-carotene but not vitamin A metabolites) on risk of hip and total fracture. Only prospective studies were included. We pooled data with a random effects meta-analysis with adjusted relative risk (adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 33 publications
(57 reference statements)
0
63
1
Order By: Relevance
“…It now seems probable that both low and high serum retinol levels as well as high intake of vitamin A can contribute to poor bone health and skeletal fragility (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It now seems probable that both low and high serum retinol levels as well as high intake of vitamin A can contribute to poor bone health and skeletal fragility (58).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Wu and colleagues assessed the level of vitamin A intake (in 283,930 participants) or serum retinol levels (in 8725 participants) and the risk of either hip fractures or total body fractures using relative risk estimates based on 95% confidence intervals from 12 prospective studies (58). The conclusion was that high intake of vitamin A and both low and high serum retinol levels were associated with elevated with risk of hip fracture but not total body fractures (58).…”
Section: A Number Of Cross Sectional and Longitudinal Studies Have Asmentioning
confidence: 99%
“…Table 1 is a summary of individual studies based on either increases, decreases, or no association of fracture risk or bone mineral density (BMD) to increased vitamin A intake or increased vitamin A intake/low vitamin D. The data suggest that increased vitamin A intake/low vitamin D favors a decrease in BMD and an increase in fracture risk (108110); however, the effect of increased intake of vitamin A alone appears to be less clear, with increases (25, 26, 111117), decreases (118121), and no associations (122128) to fracture risk and BMD reported. In contrast to the individual observations, a recent meta-analysis of prospective studies has suggested that high retinol intake and blood retinol levels have no effect on total fractures, but significantly increase the risk of hip fracture (129). …”
Section: Associations Between Vitamin a And Bone Mass In Humansmentioning
confidence: 99%
“…The hormone-replacement therapy and parathyroid hormone (PTH) also can increase vertebral bone-mineral density (26). Proper intake of vitamin D, vitamin A, vitamin K, calcium and protein may also improve the bone-mineral density and reduce the risk of fracture (3,(27)(28)(29).…”
Section: Radiographic Outcomesmentioning
confidence: 99%
“…Osteoporotic fracture is one of the major global burdens of diseases (1)(2)(3). Osteoporotic fractures could occur in hip, vertebrae, and limbs.…”
Section: Introductionmentioning
confidence: 99%